Effect of Boron Nitride Concentration and Morphology on Dielectric and Breakdown Properties of Cross‐Linked Polyethylene/Boron Nitride Nanocomposites. Issue 7 (9th April 2021) - Zhou, Xuguang; Yang, Jingjing; Gu, Zhenlu; Wei, Yanhui; Li, Guochang; Hao, Chuncheng; Lei, Qingquan
Abstract : Nanocomposite dielectric is considered the most promising insulation material for high‐voltage direct current cables. Herein, boron nitride nanoparticles (BNNPs) and boron nitride nanosheets (BNNSs) are used as nanofillers to study the effect of nanofiller concentration and morphology on the electrical properties of cross‐linked polyethylene (XLPE) composite based on experiments and simulation. The experimental results indicate that nanofiller concentration has a great influence on permittivity, while the influence of the morphology at the same concentration is small. The maximum relative permittivity occurs at 1 wt%. They are 2.35 and 2.32, respectively, for XLPE/BNNSs and XLPE/BNNP, increasing by about 11% and 9% than that of XLPE matrix. The morphology of BN significantly influence the breakdown performance, and the breakdown strength of the nanocomposite increases first and then decreases with the increase in doping concentration. The maximum breakdown strength of the composite occurs at 0.5 wt%. They are 403.8 and 349.2 kV mm −1, respectively, for XLPE/BNNSs and XLPE/BNNP, which is about 33% and 13% higher than that of XLPE matrix. Molecular simulations show that the free volume of XLPE/BNNSs is lower than that of XLPE/BNNP. In addition, the sheet structure can effectively block the carrier transport and prolong the discharge path. Abstract : Effect of boron nitride (BN) filler concentration and morphology on the dielectric and breakdown characteristics of cross‐linked polyethylene (XLPE)/BN nanocomposite are investigated by the experiments and molecular simulations. The experimental results indicate that nanofiller concentration has a great influence on permittivity and breakdown performance, while the morphology has a more significant effect on the breakdown performance.